STRUCTURAL ECONOMIC STUDY OF BALI PROVINCE THROUGH SHIFT SHARE METHOD AND KLASSEN TYPOLOGY - Eka Purna Yudha; Ghina Amelia Yusuf; Ratu Rizki Ramadhina; Sifa Faujiah; Indah Kartika Nurjanah; Jordan W.P Matondang; Desy Faramitha (Proceeding of International Seminar on Agricultural Conservation and Cultural Heritage, 2025)
This study aims to analyze the dynamics of growth and economic structure between regions in Bali Province using the Shift Share Analysis, Klassen Typology, and Williamson Index approaches. The Shift Share method is used to evaluate the contribution of national growth, the influence of industrial mix (proportional shift), and competitive advantage (differential shift) on changes in economic sectors in districts/cities in Bali. The Klassen Typology is applied to classify economic sectors into four categories: advanced and rapidly growing sectors, advanced but constrained sectors, potential sectors, and lagging sectors. The analysis reveals that there are consistent leading sectors supporting regional economic growth, such as the public administration sector, other services, and agriculture. However, the Williamson Index of 0.40 indicates that there is still moderate economic development disparity between regions in Bali. This disparity is generally driven by the concentration of development in areas dominated by the tourism and service industries. This study suggests the need for a more equitable and sustainable development strategy, focusing on the development of potential sectors and enhancing the competitiveness of strategic sectors across all districts/cities in Bali Province.